Associations of Plasma and CSF Osteocalcin Levels With CSF ATN Biomarkers and Cognitive Functions in Alzheimer's Disease - Xian‐Le Bu; Zhuo‐Ting Liu; Jia‐Yan Xin; Mei Huang; Yu‐Di Bai; Jin Zhou; Yun‐Yu Bao; Jiang‐Hui Li; Zhi‐Hao Liu; Gui‐Hua Zeng; An‐Yu Shi; Dong‐Wan Chen; et al. (MedComm)
ABSTRACT Animal studies have shown that osteocalcin (OCN), a hormone derived from bone, plays a vital role in brain development and cognitive function. However, its potential connection to Alzheimer's disease (AD) pathology in humans remains largely unexplored. This cross‐section study included 238 cognitively unimpaired participants, 26 mild cognitive impairment (MCI) patients, 54 AD dementia patients, and 32 patients with non‐AD neurodegenerative diseases. Plasma and cerebrospinal fluid (CSF) levels of OCN were measured by enzyme‐linked immunosorbent assay kits. In the clinical diagnosis‐based subgroup, plasma and CSF levels of OCN were significantly higher in MCI and AD dementia compared with cognitively unimpaired participants. In the ATN framework‐based subgroup, plasma and CSF OCN levels were significantly elevated in Aβ‐positive participants, including those in the preclinical stage of AD. Both plasma and CSF OCN levels were negatively correlated with CSF Aβ42 and positively correlated with CSF total‐tau and phosphorylated‐tau181/Aβ42. In addition, OCN mediated the relationship between Aβ pathology and tau pathology. Notably, OCN levels in plasm and CSF were also negatively associated with cognitive functions. This study provides clinical evidence linking OCN to AD, suggesting that OCN may be associated with brain Aβ deposition, tau hyperphosphorylation and neurodegeneration.